Paleoenvironment records from Lake Baikal VER99G12 sediment core - Nagayoshi Katsuta (PANGAEA, 2023)
Here we present the paleoenvironment records of biogenic silica content, total organic carbon content, and C/N molar ratio in sediment cores collected from Lake Baikal in 1999, in order to reconstruct the paleoenvironment changes during the periods from last glacial period to Holocene. The biogenic silica content was quantified by ICP-AES analysis and the total organic and nitrogen was determined using CHNS coder.